Management of Obesity in Children - Gupta, Rajeev (British Journal of Healthcare and Medical Research, 2024)
The management of childhood obesity requires a comprehensive and multidisciplinary approach that includes lifestyle modifications, behavioural interventions, parental involvement, community-based interventions, and healthcare provider support. Continued research and development of innovative therapies and interventions, such as those targeting the gut microbiome and brain stimulation, may further advance the field and improve outcomes for affected children.